Documentation and microbial trailing of Puto Tabla-making process - Delos Reyes, Mary Blaise G.; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Rice cake -- Philippines; Rice products -- Philippines; Puto tabla